Peningkatan Kompetensi Sumber Daya Manusia E-BMD untuk Mewujudkan Public Service Excellence - Tita Veby Wulansari; Hayat Hayat; Retno Wulan Sekarsari (Idarotuna : Journal of Administrative Science, 2026)
The use of information technology to improve the effectiveness, accountability, and transparency of governance, including in the management of Regional Assets (BMD), is driven by digital transformation in government administration. Electronic Regional Assets (E-BMD) is an electronic-based asset management system implemented by the Malang City Government through the Regional Finance and Assets Agency (BKAD). The capabilities of the human resources running this system have a significant impact on the success of its implementation. To achieve Public Service Excellence in the Malang City BKAD, this study aims to assess the capabilities of human resources in operating E-BMD, identify supporting and inhibiting factors, and investigate their roles. A descriptive qualitative methodology was employed in this study. In-depth interviews, observations, and documentation of staff members involved in E-BMD management were used to collect data. Afterward, an interactive data analysis model with triangulation of sources and methods for validity testing was used to examine the data. The findings indicate that human resource competency in E-BMD operations is quite strong, as evidenced by work attitudes, knowledge, and skill mastery. Training, technical advice, mentoring, organizational support, and employee dedication all contribute to developing competency. Operator changes, varying user capabilities in information technology, and potential data entry errors are examples of inhibiting factors. In regional asset management, equipment competency has been shown to improve asset data accuracy, administrative effectiveness, accountability, and transparency. To enable effective E-BMD implementation and achieve Public Service Excellence, enhancing human resource capabilities is strategically crucial.